Evaluation of the GEKO Turbulence Model for Whole Aircraft Drag Prediction - Stuart, Charles (My University, 2025)
The aim of this study was to evaluate the Generalized k-ω (GEKO) turbulence model’s ability to be calibrated to improve the accuracy of the resolved drag polar for a whole aircraft geometry. The GEKO turbulence model provides a number of user configurable free parameters capable of being calibrated to better represent a given analytical setup. A global and local study was conducted on the DLR F6 geometry and validated using experimental results collected by ONERA during a wind tunnel test campaign. An ideal wind tunnel computational domain was constructed allowing for these studies to be conducted for several angle of attack design points. A calibration framework was constructed using a Box Behnken Design of Experiments (DoE) scheme to generate 21 parameter combinations, with a fine- tuning DoE scheme used to further study the influence of the parameters. A global analysis was carried out by simulating the geometry’s drag polar over seven angle of attack design points, allowing for the selection of the combination of parameters that returned the highest accuracy and solver stability from the analysis of the tuning results to be examined. The effects of the GEKO model’s parameters on the development of flow features and the modification of the predicted far field effects were also assessed. Further analysis was conducted using coefficient of pressure data derived from experimental results on the inboard and outboard sides of the pylon to assess the calibrated model’s ability to predict the local flow field.
AIAA SCITECH Forum & Exposition
PUBLISHED
Orlando, USA